The location of arabinosyl:hydroxyproline transferase in the membrane system of potato tissue culture cells. - Owens, R; Northcote, D (1981)
Incubation of a particulate preparation from potato tissue culture cells with UDP-beta-L-[1-3H] arabinose yielded a glycoprotein fraction containing labelled material with the characteristics of hydroxyproline arabinosides. The sugar-protein linkage was resistant to hot alkaline hydrolysis, and the hydrolytic products showed similar electrophoretic and chromatographic behavior to authentic hydroxyproline-arabinosides prepared from potato tissue culture cell walls. Incorporation of arabinose into glycoprotein was stimulated by the addition of de-arabinosylated potato lectin. The product of the incubation co-migrated with native potato lectin on sodium dodecyl sulphate/polyacrylamide-gel electrophoresis. The subcellular distribution of the arabinosyl-transferase was investigated by fractionating potato tissue culture membranes on a discontinuous sucrose gradient in the presence or absence of Mg2+. Under both fractionation conditions the highest specific activity of the enzyme was found in the Golgi-enriched fraction. The results are discussed in relation to the synthesis of the hydroxy-proline-rich glycoprotein component of plant cell walls.